Funding Dynamics in Crowdinvesting - Lars Hornuf; Armin Schwienbacher (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We use hand-collected data from four German crowdinvesting portals to analyze what determines individual investment decisions in crowdinvesting. In contrast with the crowdfunding campaigns on Kickstarter, where the typical pattern of project support is U-shaped, we find crowdinvesting dynamics to be L-shaped. The evidence shows that backers base their investment decisions on information provided by the crowdinvesting portals as well as the behavior and comments of other investors. Furthermore, crowd investors engage in herding behaviour. These findings offer support for adequate information disclosure requirements that are consistent with ongoing regulatory reforms such as the JOBS Act in the United States, but that behavioral components may also affect investment decisions of the crowd.
Keywords: G11; M13; K22; 330